1998
DOI: 10.1001/jama.280.10.921
|View full text |Cite
|
Sign up to set email alerts
|

Ability to Obtain Medical Care for the Uninsured

Abstract: Context.-Communities differ in the way that medical care for medically indigent persons is organized and delivered, which is likely to result in differences across communities in the ability of uninsured persons to obtain medical care. Changes in the health care system, many of which are driven locally, may further exacerbate these differences. Objective.-To examine the extent of variation across US communities in the ability of uninsured persons to obtain medical care and the extent to which health status and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…This is similar to previous studies that reported higher levels of unmet need and lower rates of health care utilization for low income people compared to middle to high income people [16, 17, 18, 19, 20]. And, indeed, this is borne out, with these US studies identifying uninsured and low income as two of the strongest correlates of unmet need [2123, 24, 25, 26, 27, 28, 2931, 32]. In countries with universal health care coverage, such as UK, Germany, and Canada, research on unmet need has been less extensive than in the United States, perhaps because of the relative lack of direct cost-based barriers to care.…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to previous studies that reported higher levels of unmet need and lower rates of health care utilization for low income people compared to middle to high income people [16, 17, 18, 19, 20]. And, indeed, this is borne out, with these US studies identifying uninsured and low income as two of the strongest correlates of unmet need [2123, 24, 25, 26, 27, 28, 2931, 32]. In countries with universal health care coverage, such as UK, Germany, and Canada, research on unmet need has been less extensive than in the United States, perhaps because of the relative lack of direct cost-based barriers to care.…”
Section: Discussionsupporting
confidence: 89%
“…Our results also suggest an asymmetrical relationship between ER and office-based visits-a physician visit appears to diminish the probability of a later ER visit-while ER visits may result in a referral to a physician for follow-up care. For the urban uninsured, we confirm and extend earlier work (Cunningham and Kemper 1998) reporting lower access to care among the urban uninsured living in areas where managed care penetration is high.…”
Section: Discussionsupporting
confidence: 85%
“…Previous research has documented wide variation in access to medical care among uninsured individuals living in different communities (Cunningham et al 1998) and various studies have linked these access differences to variation across areas in managed care penetration, the percent of the local population that is uninsured, safety net capacity, and the location of safety net providers (Long and Marquis 1999;Cunningham 1999;Cunningham 2004a, 2004b;Cunningham and Hadley, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study analyzing the Community Tracking Study Household Survey data found that uninsured persons living in communities with the highest percentage of uninsured persons were 2 times more likely to report difficulties in obtaining care. 29 While personal health insurance is an important enabling factor for access to care, our results indicate that, at the contextual level, the overall health insurance coverage rate in a community was an important enabling factor for preventive diabetes care services. This finding may reflect the need for health care delivery organizations to encourage and coordinate use of preventive diabetes care services.…”
Section: Discussionmentioning
confidence: 67%